Job Displacement, Disability, and Divorce - Charles, Kerwin Kofi; Stephens, Jr., Melvin (Journal of Labor Economics, 2004)
Earnings shocks should affect divorce probability by changing a couple’s expected gains from marriage. We find that the divorce hazard rises after a spouse’s job displacement but does not change after a spousal disability. This difference casts doubt on a purely pecuniary motivation for divorce following earnings shocks, since both types of shocks exhibit similar long‐run economic consequences. Furthermore, the increase in divorce is found only for layoffs and not for plant closings, suggesting that information conveyed about a partner’s noneconomic suitability as a mate due to a job loss may be more important than financial losses in precipitating divorce.